Efeito do fenofibrato sobre o metabolismo de ratos com ousem indução de esteatose hepática - Adaliene Versiani Matos Ferreira (2007)
The experiments reported here were designed to study the effect of fenofibrate (stimulant of peroxisome proliferator-activated receptor á - PPARá) and hepatic steatosis induced by orotic acid administration on the metabolism of adipose tissue and liver. Wistar male rats were divided into 4 experimental groups: 1) fed a balanced diet (C); 2) fed a balanced diet plus 100 mg.Kg-1bw.day-1 fenofibrate (C+F) 3) fed a balanced dietsupplemented with 1% orotic acid (OA); 4) fed C diet containing 1% OA plus 100 mg.Kg-1 bw.day-1 fenofibrate (OA+F), which were fed during 9 days. Fenofibrate lowered body weight gain and adiposity, plasma triglyceride and total cholesterol but had no influence on food intake, plasma leptin, glucose, glycerol, free fatty acid (FFA) and insulin levels when compared to control animals. The activity of lipoprotein lípase (LPL) of treated animals decreased 50 % in epididymal adipose tissue. In this study, we have shown a 34 % decrease of epididymal adipose tissue de novo lipogenesis by fenofibrate compared to C. The glucose uptake was also evaluated by adipocyte incubation with deoxyglucose (2-DG). Fenofibrate treatment increased the glucose uptake in basal or insulinstimulated adipocytes when compared to C. This effect was not due to increased GLUT-4 protein content on adipose tissue. The results also demonstrate that fenofibrate increased the mRNA expression of ACO and PPARá in the liver and CPT-1and ACO in the adipose tissuewhen compared to control animals. The administration of OA to rats for 9 days induced significant increase in total fat liver content (160%) and decreases in plasma TG concentration (30%) and total cholesterol(28%) compared to control animals. Fenofibrate administration to rats fed OA (OA+F) prevented fat liver induction and reduced the plasma triglyceride (50%), and cholesterol (46%) concentrations in relation to the not treated group (OA). Consistently, histological examination of the liver from OA rats showed marked lipid accumulation whereas the treatment with fenofibrate in these animals prevented the development of fat liver. OA Abstract v treatment did not change de novo lipogenesis, however, fenofibrate administration caused a 40% decrease in the lipogenic rates in adipose tissue from OA+F treated rats. The results showed 40% increase in LPL activity in epididymal adipose tissue from OA treated rats when compared to C group while the fenofibrate treatment (OA+F) reduced in 50% the LPL activity in relation to OA group. OA administration enhanced the adipocyte glucose uptake in basal or insulin-stimulated conditions compared to control group. This effect was due, at leastin part, to an increase in the adipose tissue GLUT-4 protein content of OA treated rats. The fenofibrate treatment (OA+F) did not change the glucose uptake in basal or stimulated adipocyte when compared to OA animals. The liver mRNA expression of PPARá and ACO were 85% and 68% decreased in OA treated group when compared to control group,respectively. The fenofibrate treatment (OA+F) increased the liver PPARá and ACO expression whereas the CPT-1 expression was not altered when compared to the not treated group OA.In summary, we provide evidence that fenofibrate decreases the hepatic steatosis induced by orotic acid administration through enhancement of lipid catabolism in rat liver. This effect is probably mediated by PPARá, mainly through the induction of the target enzyme ACO involved in hepatic lipid metabolism. Although both the peroxisomal and the mitochondrial compartments contribute to increased oxidation of fatty acids, our data did not support a role of mitochondria in wasting energy, which is instead an intrinsic property of peroxisomal â-oxidation. Besides its effects on liver, fenofibrate seems to play a relevant role on the metabolism of adipose tissue which may contribute to decrease adiposity, probably as a result of the local increased fatty acid oxidation in the tissue, and improve the Glucose uptake by adipocyte.